ANALISIS STRUKTUR BANGUNAN YANG DITINJAU DARI TANGGA DARURAT PADA PUSAT PERBELANJAAN MESRA INDAH MALL SAMARINDA - Muhammad Septian Hadi; Baju Widjasena; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2015)
Fire may cause loss of life, material, and valuable assets or other properties. Stage in planning is the most important element in conducting prevention efforts as well as tackling the fires, which were done by performing physical design builds in accordance with standards. Emergency stairs are the means by which created, in order to assist the occupants in multi-storey building to be able to get out safely from inside the building. Emergency stairs need to consider making a good planning in general or the Interior should meet the standards. The purpose of this study was to described the factual building structures condition that reviewed by the application of fire escape stairs as the prevention of fire incident at Mesra Indah Mall Samarinda. This study was using a qualitative study with descriptive analysis approach. Subjects of this study were Securitis of Mesra Indah Mall as triangulation informants, Manager on Duty and Operational Manager of Mesra Indah Mall as the main informants. The data was collected by indepth interview with the help of interview guidance. The results showed that as the reviewed of the slant of were the risers and the dimension standard of the fire escape stairs are not suitable with Peraturan Keputusan Menteri Pekerjaan Umum No.10 Tahun 2000. On the other hand, the fire escape stairs constructions and reviewed by the fire escape stairs location, it had been suitable with Peraturan Keputusan Menteri Pekerjaan Umum No.10 Tahun 2000. Mesra Indah Mall should take an action to improve the fire mitigation and fire prevention, that was improvement of the evacuation routes by remove the unused items that located at fire escape stairs lane.